Pemberdayaan Masyarakat melalui Perbaikan Sistem Pemeliharaan Sapi di Nagari Ampang Pulai, Pesisir Selatan - Tinda Afriani; Jaswandi Jaswandi; Dwi Yuzaria; M Ikhsan Rias (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The cows are one of the ruminants that have the largest contribution as a producer of meat and for meeting the needs of animal protein. Some of the factors that can affect the lack of success of a cattle farm are the extensive rearing, limitation of cage’s fasilities, bad quality of sanitation, and lack of reproduction knowledge by farmers. The purpose of this service activity was to provide knowledge and skills of local farmers in terms of toward intensive farming, based on cowshed quality, sustainable of feed and roughage, and optimal reproduction of the cows. It hopes to increase the income of local farmers further. The activity was carried out by survey method as preparation step, counseling, training, coaching, and evaluation of program. The activity was attended by members of farmer group of Batu Kalang Indah and personnel of Nagari Ampang Pulai, Pesisir Selatan Regency. The community servant shared good practices system of cow’s farm including maintenance of cages, sanitation, feeding management and roughage’s fermentation, and reproduction skills. The participants showed enthusiasm learning during training and counseling about the livestock management. It is hoped that can provide proper information about cattle farming intensively that can be applied sustainably by targeted farmer’s group.